The effect of the bend on the discharge coefficient of a triangular side-weir - Cosar, A; Agaçcioglu, H; Üç, S (A A BALKEMA PUBLISHERS, 2000)
A side weir, also used as a lateral intake structure is a free overflow weir set into the side of a river or channels which allows to spill a part of water over side. Side-weirs are generally used in channel systems to be able to control water levels during floods, as storm overflows from urban sewage systems, and as head regulators of distributors. There are a large number of studies for side-weirs, which are mostly on straight channels. The same, however, can not be mentioned for side-weirs on curved channels. The present experimental study focuses on the investigation of discharge coefficient of the apex angle 120 degrees of sharp crested triangular side-weirs placed on various locations along a 180 degrees bend. The triangular side-weir discharge coefficient along the bend was found to depend on the upstream Froude number and the overflowed length of the side-weir.
Keywords: discharge capacity; lateral intake; overflow; spill; apex angle; Engineering; Mathematics; Water Resources